Paying it forward: short-term impacts of a livelihoods program with built-in spillovers - Thompson, William (Heifer International, 2019)
Presented by William Thompson (Heifer), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.